PENGARUH KECANDUAN GAME ONLINE TERHADAP INTERAKSI SOSIAL DI KOMUNITAS ANBU PROJECT - Fira Sayyidatina Fatimah (Program Studi Bimbingan dan Konseling, 2022)
Online game addiction is an excessive attitude in playing games, where users will continue to play games that will have a bad impact, one of which is social interaction, social interaction is a dynamic relationship, the relationship between individuals, individuals and groups. This study aims to determine the effect of online game addiction on social interaction. The method used in this research is primary data from the questionnaire results. The data processing technique in this research is simple linear. The sample of this research is anbu project. The results of this study indicate that online game addiction has a significant effect on social interaction of 0.068.